Thermophilic lignin degrading enzymes from actinomycetes for biotechnological applications - Mhlanga, Chido Yvonne Lois (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2002)
Phenolic residues which accumulate in the environment as a result of agro-industrial practices has resulted in the need to find and use Eco-Friendly techniques, rather than the traditional methods of burning or burying this kind of waste. Bioremediation and bioconversion are attractive alternatives using whole cell or enzyme-based systems. The aims of this project were to isolate and uses thermophilic Actinomycetes, which produce thermo-tolerant oxidoreductase enzymes, which can be used to bioconvert a model industrial phenolic waste commonly genersated in the wine-making industry of South Africa. Current research in bioconversion and bioremediation focuses on mesophilic microbes in that their enzymes can catalyse reactions at higher temperatures without affecting its activity and lower contamination levels. Three novel Actinomycete isolates were isolated (RU-A0l , RU-A03 and RU-A06) from a compost site and characterized using a combination of conventional identification techniques and 16S rDNA methodology to identity the three isolates. All three isolates belong to the Streptomyces clade. In addition, five known Actinomycetes were selected from an internation culture collection and also screened for oxidoreductase activity in comparision to the three novel isolates. Although the five isolates were selected based on their ability to produce oxidoreductase enzymes, unexpectedly, no activity was detected. Screening assays for peroxidase, polyphenol oxidase and laccase on RU-AO 1, RU-A03 and RU-A06, showed that all three isolated produced peroxidases and peroxidases but no laccase. Substrate specificity studies revealed that the most suitable substrates to determine peroxidase and polyphenol oxidase activity on these isolates were catechol for polyphenol oxidase, 2,4-dichlorophenol for peroxidases and veratryl alcohol for lignin peroxidases. Previous studies have indicated that peroxidases and polyphenol oxidases are produced in Actinomycetes during the primary stage of growth. This was the case with RU-AOI , RU-A03 and RU-A06. Growth rates were higher that other Actinomycetes, with maxImum biomass being reached at 36 hours for the isolates RU-AOI and RU-A06 and 48 hours for isolate RUA03. pH studies showed that the three isolates were adaptable and could grow over a broad pH range. Catabolism studies of phenolic model compounds showed that the three isolates were capable of catabolizing the model phenolic compounds within a period of 24 hours. Further studies were carried out to determine the effect of these microbes and their enzymes in whole cell and enzyme-based systems on a model phenolic waste, graoe waste consisting of compressed grape skins, pips and stalks. Whole cell studies showed that the isolates were capable of bioconverting the waste at a maximum concentration of 30% grape waste (vol:vol). Peroxidase and polyphenol oxidase activity increased indicating induction of these enzymes in the presence of phenolic compounds, with a maximum increase of up to 15.9 fold increase in extracellular lignin peroxidase activity in RU-AO1. HPLC and phenolic determination assays indicated that bioconversion of the phenolic grape waste had occurred in the presence of the three isolates. Attempts were made to isolate and identify a peroxidase or phenol oxidase gene from one the isolates. As bacteria, Actinomycetes are amendable to gene manipulation making them suitable candidates for methods such as site directed evolution in comparison to fungi. Two clones were selected for sequencing based on positive activity results when assayed for peroxidase activity. However the resultant sequences did not identify a functional gene sequence. Southern Blotting was then carried out to determine the nature of the peroxidase gene. Previous studies have been focused on the catalase-peroxidase gene (CalC gene) found Actinomycetes and other bacteria. A probe was developed from the CalC gene. No hybridization occurred with any of the enzyme restricted DNA from the three isolates. The implications of these results are that the peroxidase genets in the three isolates are in fact lignin peroxidase in nature. This project has the potential in the bioconversion of phenolic wastes and is the first description of the use of thermophilic Actinomycetes in the bioconversion of an industrial phenolic waste.
Keywords: Actinomycetales -- Biotechnology; Lignin